Fluid‐Driven Soft CoboSkin for Safer Human–Robot Collaboration: Fabrication and Adaptation. (22nd March 2021) - Heng, Wenzheng; Yang, Geng; Pang, Gaoyang; Ye, Zhiqiu; Lv, Honghao; Du, Juan; Zhao, Guodong; Pang, Zhibo
Abstract : Sensitive Robot Skin In article number 2000038, Geng Yang and co‐workers present a fluid‐driven soft robot skin with sensing and actuating function that is successfully applied to a collaborative robot. The two arms illustrated on the cover attempt to express the unintended human‐robot collision and the contact force sensing process of the CoboSkin. The Tai Chi diagram is composed of an array of two key enabling components of the CoboSkin, including the sensitive cells for force sensing and actuating cells for stiffness control. The Tai Chi diagram represents the harmonious relationship not only between humans and robots during human‐robot collaboration, but also between the sensitive function and controllable stiffness of the CoboSkin.